Dekonstruksi Spekulasi Hukum: Kajian terhadap Wasiat Beda Agama dari Sudut Pandang Hukum Islam: Deconstruction of Legal Speculation: a Study of Different Religious Wills from an Islamic Legal Perspective - Asrul Hamid; Lailan Nahari; Hsb, Zuhdi; Ritonga, Raja; Nst, Andri Muda (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
This study aims to find out the will law of different religions according to Islamic law so that it can be used as a comprehensive reference in solving the problems of will law of different religions. This research is a descriptive literature research that describes matters relating to testaments of different religions by tracing the literature according to the research theme. Sources of data used are journals, books and research results. The analytical method uses qualitative analysis and is then analyzed comprehensively in finding research results. The results of this study indicate that although there are differences of opinion among scholars regarding the will of different religions, if you look at the Qur'an there are no verses that prohibit inheritance from different religions. A testament to different religions must be seen as a form of helping fellow human beings as a form of human brotherhood regardless of their belief background.